Who's afraid of the senses? Organization, management and the return of the sensorium. Issue 4 (September 2022) - Beyes, Timon; Cnossen, Boukje; Ashcraft, Karen; Bencherki, Nicolas
Organization and management are the perpetual, and perpetually fraught and resisted, ordering of sense experience. However, banning the senses into the outside of thought, and of organizational analysis, was – and to a large degree still is – the default and mostly implicit and unquestioned mode of thinking and studying organization and management. Introducing the special issue on 'The Senses in Management Research and Education', this essay historicizes and contextualizes the neglect of the senses, dwells upon possible reasons for keeping the sensory at bay and discusses recent attempts to remedy this situation. The contributions to the special issue are introduced into this context. In conclusion, we speculate on what might happen next.